2018
DOI: 10.1002/2017gl075904
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Expressions for Thermo‐Osmotic Permeability of Clays

Abstract: In this study, a new formulation for the thermo‐osmotic permeability of natural pore solutions containing monovalent and divalent cations is proposed. The mathematical formulation proposed here is based on the theoretical framework supporting thermo‐osmosis which relies on water structure alteration in the pore space of surface‐charged materials caused by solid‐fluid electrochemical interactions. The ionic content balancing the surface charge of clay minerals causes a disruption in the hydrogen bond network wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In particular, the molecular mechanisms of thermo-osmotic flows, generated at interfaces by thermal gradients, have been explored recently. , Notably, we have shown that standard descriptions of thermo-osmosis based on irreversible thermodynamics had to be complemented to take into account interfacial hydrodynamics (stagnant layer or liquid–solid slip).…”
mentioning
confidence: 99%
“…In particular, the molecular mechanisms of thermo-osmotic flows, generated at interfaces by thermal gradients, have been explored recently. , Notably, we have shown that standard descriptions of thermo-osmosis based on irreversible thermodynamics had to be complemented to take into account interfacial hydrodynamics (stagnant layer or liquid–solid slip).…”
mentioning
confidence: 99%
“…Some theoretical estimations of the thermo-osmotic conductivity have been reported in literature. 48,49 On the basis of this, to explore the influence of the thermo-osmotic conductivity on the coupled THM consolidation response of the soil, 6 cases with different S w , are compared in Figures 14-16, where the smear effect is not considered and k represents the hydraulic conductivity of the soil. It can be observed from Figure 14 that altering the thermo-osmotic conductivity does not affect the development of the temperature increment.…”
Section: Parametric Analysismentioning
confidence: 99%
“…It is the clay soils used in geobarriers that are known to have the properties of semipermeable membranes [7,28]. A new theoretical explanation of thermo-osmotic filtration of solutions in clays is proposed in [11]. However, the authors do not deviate from the law for the rate of filtration known from the scientific literature which takes into account thermal osmosis:…”
Section: Introductionmentioning
confidence: 99%
“…According to the equation, the thermo-osmotic permeability is k T = k∇H/T (P a • m 2 /K) [11]. Most often, ∇H > 0 in clays, and fluid flow occurs in the direction of decreasing temperature, but negative values have also been reported.…”
Section: Introductionmentioning
confidence: 99%